21.8k views
5 votes
Help 69 points

36 - 7p = -7 ( p - 5)
a) No Solution
b) One Solution
c) Infinite Solutions

User Aditi K
by
4.5k points

2 Answers

6 votes

Answer:

a) No Solution

Explanation:

36 - 7p = -7(p - 5)

36 - 7p = -7p + 35

1 - 7p = -7p

1 = 0p

so a) No Solution

User GreenGiant
by
4.9k points
9 votes

Answer:


36 - 7p = - 7(p - 5) \\ 36 - 7p = - 7p - 7 * - 5 \\36 - 7p = - 7p + 35 \\ p \: terms \: togather \\ - 7p + 7p = 35 - 36 \\ 0p = - 1 \\ here \: we \: \: have \: 0p \\ so \: no \: solution \\ option(a) \\ thank \: you

User Etienne Tonnelier
by
5.9k points